On Visibility and Legitimisation of Languages: The ‘Linguistic Landscape’ in Adaama, Ethiopia - Wolff, H. Ekkehard; Berhanu, Sileshi; Fulea, Getinet (Aethiopica, 2013)
With a focus on the city of Adaama (formerly: Nazret), the biggest urban agglomeration in Oromia Regional State, the paper addresses the “linguistic landscape” which is indicative of the overall sociolinguistic situation of a polity. Language use in the public space has not only practical-instrumental, but also historical, political, juridical, and most of all psycho-sociological dimensions, the latter relating to the symbolic value of written language use. The paper deals with multilingual graphic representations on public commercial and private sign-boards, advertisements, and notices in Adaama city, with an additional focus on the situation on the campus of Adama Science and Technology University. Under the chosen theoretical framework, it analyses language visibility in terms of language legitimisation, both in terms of peoples’ attitudes and based on official documents regarding language status and language use in present-day Ethiopia, such as the Education and Training Policy (1994), the Constitution of the Federal Democratic Republic of Ethiopia (1995), the Revised Constitution of Oromia Regional State (2001/2006), and the Higher Education Proclamation (2009). The primary focus of the paper is on the status, functions, and representations of Afan Oromo, including a review of the major historico-political changes affecting this language from Imperial Ethiopa (before 1974), the Därg period (until 1991), and under the new Constitution of the FDRE (since 1995). The paper also deals with linguistic and graphic issues concerning the “orthographic” representations of the four languages used: Afan Oromo, Amharic, Arabic, and English, involving three different graphic systems: Fidäl (Abugida), Arabic, and Roman.